UPAYA PENCEGAHAN STUNTING MELALUI PROGRAM GEBYAR PEKAN KESEHATAN DI DESA SENGKATI BARU - Fitri, Adelina; Aswin, Budi; Ningsih, Vinna Rahayu; Putra, Ashar Nuzulul; Rahmat, Andree Aulia; Putri, Fitria Eka; Hubaybah, Hubaybah (Prodi Ilmu Kesehatan Masyarakat, FKIK Universitas Jambi, 2024)
Stunting is a serious public health problem in many developing countries, including Indonesia. This research aims to evaluate the effectiveness of the